Nonlinear hearing aids and verification of fitting targets. - Fabry DA (Trends in Amplification, 2003)
This paper addresses the issue of initial verification of hearing aid gain and output for nonlinear hearing aids. Specifically, 'urban legend' has it that nonlinear hearing aids with digital noise reduction circuitry may not be accurately measured using functional gain and/or probe microphone measures. Discussed are the advantages and disadvantages of both measurement strategies, and how they may be used to 'acoustically match' hearing aids to individual patients. An evaluation protocol that employs both optimal aided thresholds and probe microphone measurements to assess gain, output, and audibility in hearing-impaired patients.